Interpersonal Karma: A Note - Ritzinger, Justin R. (Journal of global buddhism, 2023)
It has been twenty years since Jonathan S. Walters sought to dislodge the ingrained understanding of karma as a purely individual phenomenon. Since then, interesting work has been done on this issue, but less than one might hope and much of it siloed, addressing either texts or ethnography, either this region or that one. One of the most exciting aspects of a recent symposium on lived karma was the opportunity to explore these issues with scholars of widely varied expertise. One theme that emerged is what I will term "interpersonal karma." Across the Buddhist world, we find not only that our relationships are constituted by karmic affinities, but also that in many contexts those relationships are seen as the media through which karma unfolds. These understandings not only provide frameworks for interpreting relationships but underwrite ritual technologies through which people can form, maintain, or disperse these affinities.